Toulouse, université hispanique. Des relations universitaires franco-espagnoles du Moyen Âge à l’Ilustración - Patrick Ferté (Les Cahiers de Framespa)
During the Middle Ages and the Renaissance, the attraction the university of Toulouse had for Spanish students was intense and unbroken. They were numerous on Faculties benches or chairs, in spite of war, of religious unrests and of royal prohibitions. After the lowest attendance level in the mid of the seventeenth century, exhaustive serial sources are proving that traditional transpyrenean tropism was revived and increased in the eighteenth century : after the instauration of a favourable to Castillan party Bourbon regime, who suppressed ancient catalan universities, and replaced those rebellious seats by the new and submissive university of Cervera (1717), more than 900 uncompromising Catalan students scorned it with a sort of passive resistance and they hurled themselves at Toulouse, who became again a spare campus in spite of interdicts.